USE of group sequential test methods in the survival analysis in aquaculture - Gokkus, Zeynep; Alakus, Kamil; Bilen, Soner (Elsevier BV, 2020)
Abstract The information obtained as a result of research in natural sciences should have a high statistical power, that is also valid for the field of aquaculture. The sample size needs to be increased in order to increase the statistical power of a scientific study. However, studying on large sample size may not always be possible. Therefore, many experimental designs have been developed for data collection purposes to keep the sample size minimum. Group sequential designs have been enhanced for the data entered sequentially to the trial most of the time in medicine, production, economy etc. With these designs, the studies can be early terminated and results can also be obtained the results based on with high statistical power with smaller sample size. These experimental designs are specifically applied to survival data. In the survival analysis used in the field of aquaculture, all of the samples are included at the beginning. One of the important risk in this method is the loss of most or all of the samples due to unexpected effects. If this occurs, the trial must be discontinued or repeated and procedure then becomes time consuming and expensive. To minimize these risks the use of group sequential test methods is proposed in our study. It can be done by a standard treatment (or survival etc.) group and a (or more) new treatment (or survival etc.) group(s). For this approach, 450 rainbow trout were divided into three sequential groups including 1. Control, 2. Aeromonas hyrophilia infected group and 3. Yersinia ruckeri infected group. The survival-time of each sequential run was evaluated by means of four interim analyses via a retrospective trial design. By entering new samples during the trial, both unexpected risks were minimized and continuous data was provided. After the third interim analysis, it was determined that the survival times of the three groups were significantly different from each other and the early termination of the trial was approved.
Keywords: Power analysis; Trial design in aquaculture; Sample size; Group sequential test methods; Survival analysis; 14. Life underwater